Microarray gene expression of periosteum in spontaneous bone regeneration of mandibular segmental defects - Zheyi Li (Nature Portfolio, 2017)
Abstract Spontaneous bone regeneration could occur to reestablish mandibular bony continuity in patients who underwent partial or total mandibulectomy for tumors with periosteum-preserving. However, scarce data is available related to the precise role of periosteum in this bone regeneration. Therefore we aimed to investigate the gene expression of periosteum that were involved in the mandibular bone regeneration. Mandibular segmental defects were created in six mini-pigs with periosteum preserved. The periosteum of defects and control site were harvested at 1 and 2 weeks. Gene ontology (GO) analysis showed that the mechanisms concerning immature wound healing were clearly up-regulated at week 1. In contrast, by week-2, the GO categories of skeletal development, ossification and bone mineralization were significantly over-represented at week-2 with several genes encoding cell differentiation, extracellular matrix formation, and anatomical structure development. Furthermore, Tgfβ/Bmp, Wnt and Notch signaling were all related to the osteogenic process in this study. Besides osteogenesis, genes related to angiogenesis and neurogenesis were also prominent at week-2. These findings revealed that the gene expression profile of the periosteum’s cells participating in bone regeneration varied in different time points, and numbers of candidate genes that differentially expressed during early healing stages of intramembranous bone regeneration were suggested.